Novel TEM sample preparation using XeF2 selective Etching. Issue 1659 (17th February 2014) - Ambrosini, Stefano Filo; Bowen, Leon; Mendis, Budhika; Cirlin, George; Bouravleuv, Alexey; Gallant, Andrew; Petty, Michael; Dubrovskii, Vladimir; Zeze, Dagou
ABSTRACT: We present a new approach to prepare Transmission Electron Microscopy (TEM) nanowire (NW) samples that addresses the core drawbacks of conventional techniques, which are based on mechanical polishing. The proposed method is time efficient and uses XeF2 isotropic and selective dry etching of Si to remove the host substrate from the NWs, after their embedding into a poly(methyl-methacrylate) (PMMA) matrix. Scanning electron microscopy (SEM) data suggest that NWs were grown through the gaps between the parasitic layer islands and that the stems are in direct contact with the Si substrate. This technique does not adversely affect the NWs and offers a convenient means of transferring the GaAs NWs onto other surfaces for post-process TEM analysis. It also offers excellent potential to facilitate their integration into device fabrication via a bottom-up approach, using the PMMA layer as a transfer medium.